Mekanisme Pertahanan Ego Tokoh Utama Novel “Belok Kiri Langsing” Karya: Achi Tm Tinjauan Psikologi Sastra: Ego Defense Mechanisms of the Main Character in the Novel "Belok Kiri Langsing" by Achi TM: A Literary Psychology Perspective - Triana, Ade; Kudadiri, Amhar; Marsella, Emma (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This research aims to analyze the Ego Defense Mechanism of the main character in the novel "Belok Kiri Langsing" by Achi TM. Ego defense mechanisms are psychological strategies that individuals use to deal with conflict, stress and threats faced in everyday life. In this study, the research method used was qualitative analysis of the text of the novel "Belok Kiri Langsing" with a focus on the behavior and dialogue of the main character. Sigmund Freud's psychoanalytic theory is used as a theoretical framework to understand the various ego-protection mechanisms that the main character may use. The research results show that the main character uses various ego defense mechanisms, including repression, rationalization, and sublimation, to overcome the conflict and stress he experiences. Ego becomes the dominant mechanism used by the main character to suppress painful or threatening thoughts or feelings, while rationalization is used to justify the actions or decisions taken. The formation of sublimation appears as a mechanism that helps the main character divert his psychic energy to more constructive activities. This research contributes to the understanding of character characterization in the novel "Represi" and its relevance to psychoanalytic theory. The implications of this research can be used to deepen our understanding of the complexity of human psychology as reflected in literary works.